Implementasi Smart Village Product Industrial Activity dalam Pengembangan Petani Jeruk Poncokusumo dalam Mewujudkan Sustainable Development’s Society (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2020)
This research aims to create the eradication of the poverty model by using smart village product industrial activity that will be implemented in orange farmers in Poncokusumo. This research has done in the planned method include 1) planning, 2) action, 3) evaluation and reflection. Based on data analysis that got by seminar and socialization in Poncokusumo show there are huge potentials in orange products. These products can be used as a competitive product that can be branding for Poncokusumo. This product branding called Poncosweet as a representative of the candy product. By developing this potential product can make smart village product industrial activity toward sustainable development’s society in Poncokusumo. The suggestion of this research are all stakeholder should be involved in the developing of the smart village in Poncokusumo.